Cover Feature: Probing the Catalytically Active Species in POM‐Catalysed DNA‐Model Hydrolysis (Chem. Eur. J. 35/2021). Issue 35 (7th June 2021) - Martins, Frederico F.; Sánchez‐González, Ángel; Lanuza, Jose; Miras, Haralampos N.; Lopez, Xabier; Bandeira, Nuno A.; Gil, Adrià
Abstract : A [Mo7 O24 ] 6‐ polyanion is used to catalyze the hydrolysis of a phosphoester bond, although the polyanion is not directly responsible for the catalysis. The real catalyst is produced in situ of the reaction media through the decomposition of the initial polyoxometalate leading to the [Mo2 O8 H4 ] dimeric species, which is the real catalytic species. Formation in situ of this neutral compound would explain why polyanions may approach the negatively charged environment of the phosphoester bond and produce the catalysis. The lower mass of the real catalytic species suggests a cheaper and greener chemical process. More information can be found in the Full Paper by H. N. Miras, N. A. Bandeira, A. Gil, et al. (DOI: 10.1002/chem.202004989 ).